Nanoscience and Nanotechnology: Perspectives and Overview - RAVICHANDRAN, R.; SASIKALA, P. (SCHOOL SCIENCE, 2006)
NANOSCIENCE is fast becoming one of the major areas of science. Its appeal lies in the long-dreamt-of ability to investigate and manipulate matter at the level of individual atoms and molecules. And while it is scientific curiosity that is currently driving research forward in this area, there is the tempting thought that discoveries could play key role in a future world of nano-devices and nano computers. Hence, it becomes very much essential on the part of the science teachers to get the science students exposed, enriched and motivated on this interdisciplinary field which is going to rule this knowledge society. Also efforts should be made to include this thrust area in school science curriculum appropriately, for a successful exploitation of this upcoming area.